2011
DOI: 10.5566/ias.v19.p219-222
|View full text |Cite
|
Sign up to set email alerts
|

Nephron Number in the Offspring of Rats Fed a Low Protein Diet During Pregnancy

Abstract: In experimental studies it has been shown that intrauterine growth retardation and reduced kidney growth during development are associated with significant decreases in nephron endowment. However, the results of previous studies may be inaccurate as nephron counts were obtained using a maceration technique, which can lead to breakdown of glomeruli, and other potentially biased techniques. In the present study, the total number of glomeruli (and thereby nephrons) in the offspring of rats fed a low (9%) or norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 17 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Human studies have identified a strong linear relationship between birth weight and nephron number [39], [40], [41]. Animal models of spontaneous [42], [43] and induced growth restriction [42], [44], [45] further support this association. In rodents, high glucose exposure is reported to alter kidney morphology and lead to a nephron deficit in growth restricted and normal birth weight offspring [16], [17].…”
Section: Discussionmentioning
confidence: 78%
“…Human studies have identified a strong linear relationship between birth weight and nephron number [39], [40], [41]. Animal models of spontaneous [42], [43] and induced growth restriction [42], [44], [45] further support this association. In rodents, high glucose exposure is reported to alter kidney morphology and lead to a nephron deficit in growth restricted and normal birth weight offspring [16], [17].…”
Section: Discussionmentioning
confidence: 78%
“…It is well known that a range of genetic factors and perturbations to the fetal-maternal environment 52,53 can influence nephron endowment at birth. Fetal-maternal factors include maternal nutrition, 54 56 gestational diabetes, 57 exposure to alcohol, 58,59 natural and synthetic glucocorticoids, 60 and hypoxia. 61,62 Little is known about regulation of podocytogenesis and podocyte endowment at birth, although we recently reported that mild hypoxia in mice during gestation gives rise to male offspring with low podocyte endowment, although female offspring were not affected.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies in the USA have reported that body weight and WC were reduced when protein was consumed above the recommended daily allowance [0.8 g/kg body weight (BW)] [53]. It has been noted in animal models, that pregnant rats consuming a low protein diet were more prone to GDM and to having offspring with a low birthweight [54, 55]. In our study, we found a significant interaction between the metabolic-GRS and protein energy (%) on log WC, where individuals consuming a low protein diet, despite carrying 5 or more risk alleles, had a lower waist to hip ratio compared to individuals carrying 4 or less risk alleles.…”
Section: Discussionmentioning
confidence: 99%